Arctocypris fuhrmanni, n. gen., n. sp. (Crustacea, Ostracoda, Eucypridinae) from Spitsbergen (Norway) - Petkovski, Trajan K.; Scharf, Burkhard; Keyser, Dietmar (Zootaxa, 2016)
Material from Spitsbergen (Norway) collected by Spitzenberger (1996) was reinvestigated. A new genus Arctocypris and a new species Arctocypris. fuhrmanni n. gen. n. sp. are described in the present paper. A key to the genera of the subfamily Eucypridinae is provided. At the moment Arctocypris n. gen. comprises four species: Arctocypris arctica (Olofsson, 1918) comb. nov.; A. dulcifons (Diebel & Pietrzeniuk, 1969) comb. nov.; A. foveata (Delorme, 1968) comb. nov. and Arctocypris fuhrmanni n. gen., n. sp.